2015
DOI: 10.1002/cbm.1958
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with physical or sexual intimate partner violence perpetration by men attending substance misuse treatment in Catalunya: A mixed methods study

Abstract: Intimate partner violence is common among men attending substance misuse treatment. Integrated interventions should that address both intimate partner violence and substance misuse should be considered. Areas for intervention would include reducing dominating-isolating behaviours and emotional-verbal abuse, improving communication skills, challenging gender-specific roles and believing that substance use 'causes' violent behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
3
25
0
1
Order By: Relevance
“…Similar to other studies , lifetime IPV victimisation reported by participants was also high. This may be because of participants' partners responding in self‐defence, conflicts around substance use or it may also be influenced by reporting bias.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to other studies , lifetime IPV victimisation reported by participants was also high. This may be because of participants' partners responding in self‐defence, conflicts around substance use or it may also be influenced by reporting bias.…”
Section: Discussionsupporting
confidence: 89%
“…Participants received a £10 gift voucher or monetary equivalent for their time in England only, as this was not usual research practice in Brazil. As previous studies reported a high proportion of incomplete questionnaires among this client group and similar disclosure rates of sensitive or stigmatising information (including IPV and substance use) have been reported across face‐to‐face interview and paper‐and‐pencil questionnaire , 17 (five females in England, and six females and six males in Brazil) experienced interviewers (all received 8 h training on interview administration and study protocol) administered the interviews in a private room to enhance completion rates. Men aged 18 or older, who were engaged in outpatient substance use treatment and were able to give informed consent, were eligible to participate.…”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…In any case, the high frequency of such dropouts has even been confirmed by Cox regression, which documented the confounding effects of psychopathology. Considering the kind of substance abused, some studies have shown an association of cocaine use with dropout [4145], but this has not been confirmed in studies carried out in therapeutic communities [35, 38, 46]. …”
Section: Discussionmentioning
confidence: 99%